Multiple criteria decision making approaches to assessing forest sustainability using criteria and indicators: a case study - Mendoza, G.A.; Prabhu, Ravi (2000)
This paper describe the use of multiple criteria decision tools for assessing criteria and indicators designed to evaluate sustainable forest management. Three techniques called ranking, rating, and pairwise comparisons are described and used within the framework of a generic set of criteria and indicators applied in a case study involving a forest concession in Kalimantan, Indonesia. For the case study, an assessment team consisting of national and international experts representing various disciplines was chosen to conduct an assessment of the forest concession. The criteria and indicators (C&I) developed by the Center for International Forestry Research were used as a reference. From this generic set of C&I, the assessment team made revisions to make the set more relevant to the prevailing conditions in the forest concession. This modified set was used in the assessment of the concession. Results from the study indicate that these techniques are effective tools both for selecting sets of criteria and indicators and eventually for prioritising them. The methods are highly transparent, easy to understand, and offer a convenient environment for participatory decision-making. These are desirable features of any evaluation but most especially for a complex assessment problem such as forest sustainability.